Exploring teaching strategies for training programmes in business coaching - Maritz, Jeanette; Poggenpoel, Marie; Myburg, Chris (University of the Free State, 2011)
Coaching and business coaching, in particular, is an academically immature, yet emerging discipline. While there appears to be general consensus about the requisite knowledge, skills, and attitudes of business coaches, there is currently little agreement on facilitating these competencies in the higher educational setting in order to develop the core competencies of business coaches. This qualitative study explores and describes teaching strategies to facilitate the core competencies of business coaches in business coaching training programmes. The findings indicate that the nature of business coaching practice demands a critical disposition to thinking and acting. The nature of the business coach learner as a mature adult emphasises the importance of an experiential learning environment that promotes learner reflexivity. Possible teaching strategies depend on and promote interactive discourse and real-time learning.

Afrigting, en meer spesifiek besigheidsafrigting, is ’n akademies onderontginde, maar tog ontwikkelende dissipline. Hoewel daar algemene konsensus met betrekking tot die vereiste kundigheid, vaardighede en ingesteldheid van besigheidsafrigters bestaan, is daar egter weinig eenstemmigheid oor hoe hierdie bevoegdhede op die mees toepaslike manier in die hoër opvoedkundige milieu gefasiliteer kan word ten einde die doelstellings van besigheidsafrigtingsprogramme te bereik. Die doel van hierdie kwalitatiewe studie is om moontlike onderrigstrategieë vir besigheidsafrigtingsprogramme te ondersoek en te beskryf ten einde die kernvaardighede van besigheidsafrigters te bevorder. Die bevindings dui aan dat die aard van besigheidsafrigting in die praktyk ’n kritiese benadering ten opsigte van denke en optrede verg. Omdat die leerder van besigheidsafrigting volwasse is, is dit belangrik dat die leeromgewing op ervaring geskoei word sodat dit selfondersoek kan bevorder. Die vertrekpunt van moontlike onderrigbenaderings behoort werklikheidsgebonde en deelnemende beredenering te wees
Keywords: Business coaching; Teaching strategies